Efektivitas Pengawasan Ketenagakerjaan Terhadap Upah Minimum Pekerja - Fitriani, Rizki Amalia; Satria, Rahmad; Astono, Agustinus; Mastiurlani Christina Sitorus, Angelia Pratiwi; Utomo, Setyo (Universitas Semarang, 2022)
Labor and wages are like two sides of a coin which is always a problem. The regulation of wages is regulated in Law Number 13 of 2003 concerning Manpower and confirmed through Government Regulation Number 78 of 2015 concerning Wages and Regulation of the Minister of Manpower and Transmigration Number 15 of 2018 concerning Minimum Wages. This study aims to answer the factors that cause the ineffective supervision carried out by the Technical Implementation Unit (UPT) of Labor Inspection on the provision of minimum wages for workers, as well as the efforts that can be made by the Technical Implementation Unit (UPT) of Labor Inspection in making effective supervision of the provision of minimum wages for workers through normative juridical research method (doctrinal) is an approach that views law as a doctrine or a set of normative rules (law in the book). The factors causing the ineffectiveness of the supervision carried out by the Technical Implementation Unit (UPT) of Labor Inspection on the provision of minimum wages for workers are due to limited personnel and the efforts that can be made by the UPT through: (a) conducting a sudden inspection (Sidak) to the worker s premises, and (b) impose strict sanctions on employers World Health Organization provide workers wages that are not in accordance with the minimum wage as stipulated in the laws and regulations in the field of wages. Tenaga kerja dan upah bagaikan dua sisi mata uang yang selalu menjadi permasalahan. Pengaturan tentang upah diatur dalam ketentuan terkait Ketenagakerjaan serta dipertegas melalui ketentuan mengenai Pengupahan dan Peraturan Menteri Tenaga Kerja dan Transmigrasi serta ketentuan mengenai Upah Minimum. Penelitian ini bertujuan untuk menjawab faktor yang menyebabkan belum efektifnya pengawasan yang dilakukan oleh Unit Pelaksana Teknis (UPT) Pengawasan Ketenagakerjaan terhadap pemberian upah minimum pekerja, serta upaya yang dapat dilakukan Unit Pelaksana Teknis (UPT) Pengawasan Ketenagakerjaan dalam mengefektifkan pengawasan terhadap pemberian upah minimum pekerja melalui metode penelitian yuridis normatif (doktrinal) adalah suatu pendekatan yang memandang hukum sebagai doktrin atau seperangkat aturan yang bersifat normatif (law in book). Faktor penyebab belum efektifnya pengawasan yang dilakukan oleh Unit Pelaksana Teknis (UPT) Pengawasan Ketenagakerjaan terhadap pemberian upah minimum pekerja dikarenakan keterbatasan personil serta upaya yang dapat dilakukan oleh UPT melalui: (a) melakukan Inspeksi Mendadak (Sidak) ke tempat pekerja; dan (b) memberikan sanksi yang tegas kepada pengusaha yang memberikan upah pekerjanya tidak sesuai dengan upah minimum sebagaimana diatur dalam peraturan perundang-undangan di bidang pengupahan.